Publicysta w sporach dzienników opinii w Polsce. Analiza felietonów Rafała Ziemkiewicza w „Rzeczpospolitej” - Piątek, Paulina (Wydawnictwo Naukowe WNPiD UAM, Poznań, 2011)
Editors of daily newspapers struggle every day in order to attract readers. It applies especially to opinion newspapers which represent different political views. Two leading newspapers in Poland are “Rzeczpospolita” and “Gazeta Wyborcza”. The analysis of articles published in these newspapers shows how journalists are trying to manipulate the readers. The manipulation and persuasion, used by one of the leading commentators from “Rz” – Rafał Ziemkiewicz became the object of this study. Having almost 400 columns of that author’s analyzed, it can be stated that in his writings there are elements of both manipulation and persuasion. These elements are divided into thematic groups.

Redakcje dzienników każdego dnia walczą o czytelników. Dotyczy to w szczególności gazet codziennych, nieprzypadkowo nazywanych liderami opinii, z których każda prezentuje inny punkt widzenia. Dwoma wiodącymi na rynku dziennikami są „Rzeczpospolita” i „Gazeta Wyborcza”. Poddając analizie artykuły, publikowane w obu gazetach, zauważamy w jaki sposób dziennikarze starają się manipulować opinią czytelników. Manipulacja i perswazja, wykorzystywane przez jednego z czołowych dziennikarzy, felietonistów „Rz” – Rafała Ziemkiewicza, stały się obiektem badań. Przeanalizowane, ponad 400 felietonów tego autora, pozwoliły zaobserwować w jego tekstach zarówno elementy manipulacji, jak i perswazji. Elementy te zostały podzielone w tekście w grupy tematyczne.
A Commentator on Current Affairs in the Dispute of Daily Newspapers in Poland (the analysis of Rafał Ziemkiewicz’s Feature Articles in “Rzeczpospolita”)
Keywords: Ziemkiewicz Rafał; Rzeczpospolita; publicystyka; felieton